1994
DOI: 10.1088/0031-9155/39/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Photon beam convolution using polyenergetic energy deposition kernels

Abstract: In photon beam convolution calculations where polyenergetic energy deposition kernels (EDKS) are used, the primary photon energy spectrum should be correctly accounted for in Monte Carlo generation of EDKS. This requires the probability of interaction, determined by the linear attenuation coefficient, mu, to be taken into account when primary photon interactions are forced to occur at the EDK origin. The use of primary and scattered EDKS generated with a fixed photon spectrum can give rise to an error in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…The "effective mean kernel" method ignores spectral changes of the photon beam throughout the patient geometry (e.g., beam hardening and off-axis softening) as well as spectral changes for different field sizes, and can lead to dose calculation inaccuracies. [4][5][6] In fact, several studies have found that higher accuracy was achieved when beam hardening of the kernels was taken into account in the convolution calculation. Dose errors caused by using nonhardened kernels were found to be as high as 2%-5% on the central axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "effective mean kernel" method ignores spectral changes of the photon beam throughout the patient geometry (e.g., beam hardening and off-axis softening) as well as spectral changes for different field sizes, and can lead to dose calculation inaccuracies. [4][5][6] In fact, several studies have found that higher accuracy was achieved when beam hardening of the kernels was taken into account in the convolution calculation. Dose errors caused by using nonhardened kernels were found to be as high as 2%-5% on the central axis.…”
Section: Introductionmentioning
confidence: 99%
“…Dose errors caused by using nonhardened kernels were found to be as high as 2%-5% on the central axis. [4][5][6] Although Liu et al 6 suggested that their kernel interpolation method could be used to take into account the effects of offaxis softening, there have been no studies that have quantified the effects of kernel softening with larger field sizes and greater off-axis distances for a clinical photon beam.…”
Section: Introductionmentioning
confidence: 99%
“…One is the single polyenergetic method [3][4][5][6][7][8][9][10][11][12], where the convolution is performed with the use of a single-dose kernel that is formed by use of the incident X-ray spectrum. The other is the components method [3,7,[9][10][11][12][13][14][15], where a separate convolution is performed that uses each of the multi-dose kernels that are usually formed with the use of effective X-ray spectra, by which the number of energy bins can be decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Two polyenergetic kernels are created by Terma-weighting monoenergetic energy deposition kernels 10,11 . One kernel is formed using the primary dose deposition kernels and the other is formed using the scatter dose deposition kernels.…”
Section: Introductionmentioning
confidence: 99%
“…One kernel is formed using the primary dose deposition kernels and the other is formed using the scatter dose deposition kernels. Kernel-hardening correction factors are computed and applied to Terma based on the Kerma (kinetic energy released per unit mass) to Terma ratio at depth and at the surface 10 . The dose is computed by convolving the polyenergetic Terma with the primary and scatter polyenergetic energy deposition kernels.…”
Section: Introductionmentioning
confidence: 99%